Whole‐exome sequencing reveals a novel missense mutation in the MARS gene related to a rare Charcot‐Marie‐Tooth neuropathy type 2U. Issue 2 (9th May 2018) - Sagi‐Dain, Lena; Shemer, Lilach; Zelnik, Nathanel; Zoabi, Yusri; Orit, Sadeh; Adir, Vardit; Schif, Aharon; Peleg, Amir
Abstract : Charcot‐Marie‐Tooth (CMT) is a heterogeneous group of progressive disorders, characterized by chronic motor and sensory polyneuropathy. This hereditary disorder is related to numerous genes and varying inheritance patterns. Thus, many patients do not reach a final genetic diagnosis. We describe a 13‐year‐old girl presenting with progressive bilateral leg weakness and gait instability. Extensive laboratory studies and spinal magnetic resonance imaging scan were normal. Nerve conduction studies revealed severe lower limb peripheral neuropathy with prominent demyelinative component. Following presumptive diagnosis of chronic inflammatory demyelinating polyneuropathy, the patient received treatment with steroids and intravenous immunoglobulins courses for several months, with no apparent improvement. Whole‐exome sequencing revealed a novel heterozygous c.2209C>T (p.Arg737Trp) mutation in the MARS gene (OMIM 156560). This gene has recently been related to CMT type 2U. In‐silico prediction programs classified this mutation as a probable cause for protein malfunction. Allele frequency data reported this variant in 0.003% of representative Caucasian population. Family segregation analysis study revealed that the patient had inherited the variant from her 60‐years old mother, reported as healthy. Neurologic examination of the mother demonstrated decreased tendon reflexes, while nerve conduction studies were consistent with demyelinative and axonal sensory‐motor polyneuropathy. Our report highlights the importance of next‐generation sequencing approach to facilitate the proper molecular diagnosis of highly heterogeneous neurologic disorders. Amongst other numerous benefits, this approach might prevent unnecessary diagnostic testing and potentially harmful medical treatment.